Number of consulting medical institutions and risk of polypharmacy in community-dwelling older people under a healthcare system with free access: a cross-sectional study in Japan - Toshiki Suzuki; Masao Iwagami; Shota Hamada; Tomoyuki Matsuda; Nanako Tamiya (BMC, 2020)
Abstract Background Under the Japanese free access healthcare system, patients are allowed to consult multiple medical institutions (including clinics and hospitals for general or specialist consultation) without primary care referral. This potentially increases the risk of polypharmacy. We examined the association between the number of consulting medical institutions and polypharmacy under a healthcare system with free access. Methods Via a self-administered questionnaire, we identified people aged ≥65 years with ≥1 disease and  ≥1 consulting medical institution in a Japanese city in 2016. The exposure of interest was the number of consulting medical institutions (1, 2, or ≥3) and the outcome was polypharmacy (use of ≥6 types of drugs). We performed a multivariate logistic regression analysis, adjusting for age, sex, household economy, and the number and type of comorbidities. To minimize confounding effects, we also performed propensity-score-matched analysis, categorizing patients into two groups: 1 and  ≥2 consulting medical institutions. Results Of 993 eligible individuals (mean (standard deviation) age: 75.1 (6.5) years, men: 52.6%), 15.7% (156/993) showed polypharmacy. Proportions of polypharmacy were 9.7% (50/516), 16.6% (55/332), and 35.2% (51/145) for people who consulted 1, 2, and  ≥3 medical institutions, respectively. Relative to people who consulted 1 medical institution, adjusted odds ratios (95% confidence intervals) for polypharmacy were 1.50 (0.94-2.37) and 3.34 (1.98-5.65) for those who consulted 2 and  ≥3 medical institutions, respectively. In propensity score matching, of 516 and 477 patients who consulted 1 and  ≥2 medical institutions, 307 pairs were generated. The proportion of polypharmacy was 10.8% (33/307) and 17.3% (53/307), respectively (P = 0.020). The odds ratio for polypharmacy (≥2 vs. 1 consulting medical institution) was 1.73 (95% confidence interval 1.09-2.76). Conclusions Patients who consulted more medical institutions were more likely to show polypharmacy. The results could encourage physicians and pharmacists to collect medication information more actively and conduct appropriate medication reviews. Strengthening primary care is needed to address the polypharmacy issue, especially in countries with healthcare systems with free access.